Guest Editors' Introduction. (September 2019) - Lewis, Ruth; Marine, Susan B.
In the midst of a wider resurgence of feminist activism, it is timely to ask whether current efforts to address gender-based violence (GBV) on campus are adequate. This guest editors' introduction to the special issue considers whether our attention should be on transforming, rather than simply adapting, university environments. While critiquing adaptive approaches rooted in "compliance culture", it sets out key elements of transformative approaches to GBV on campus. It introduces the articles in this special issue and their discussions about efforts to transform university environments in Canada, America and the United Kingdom. It finishes by highlighting enduring barriers to transformational work and areas for further investigation in our efforts to make institutions of higher education safe for all.